The Anatomy and Anatomical Variations of the Round Window Prechamber and Their Implications on Cochlear Implantation: An Anatomical, Imaging, and Surgical Study - Mehanna,Ahmed Mohamed (2020)
Abstract Introduction Over the last decades, there has been a tremendous increase in the number of cochlear implant recipients and, consequently, there is a recent increase of interest in the proper understanding of the anatomy of the round window (RW), which is the most important anatomical land mark during cochlear implant surgery. Objectives The present study was undertaken to assess the detailed surgical and radiological anatomy of the RW prechamber; its shape, directions, measurements, common anatomic variations, and its relationships with different surrounding structures as related to cochlear implantation. Methods A total of 20 cadaveric specimens of human temporal bone were microscopically dissected for the anatomical assessment of the measurements of the RW and its relation to surrounding structures in the tympanum. A total of 20 patients were subjected to cochlear implantation, and a radiological and surgical assessment of the anatomy of their RW prechambers was performed. Results The distances between the RW and the facial canal (FC), the jugular fossa (JF), the carotid canal (CC), and the oval window (OW) were measured. Among the cases subjected to cochlear implantation, the infracochlear tunnel was studied radiologically; the lengths of the anterior and posterior pillars were assessed, and the relation with the direction at which the RW faces was statistically analyzed. Conclusions Proper understanding of the topographic anatomy of the RW, including its direction of opening and the distances from different adjacent structures in the tympanum, is essential for a successful cochlear implantation surgery, since it can help decision-making before the surgery and is useful to avoid many complications, such as misplaced electrode and iatrogenic injury to the surrounding structures.